Promoting better family meals for girls attending summer programs - Rosenkranz, Richard R.; Dzewaltowski, David A. (My University, 2009)
Numerous cross-sectional studies and some longitudinal studies have identified the positive attributes and protective effects of the traditional family meal. Children and adolescents who frequently eat meals with their families are more likely to eat fruits & vegetables, less likely to consume fried foods, soda, or sweets, less likely to have disordered eating patterns, and less likely to be overweight. However, very few published reports evaluate programs designed to increase the frequency or quality of family meals. Therefore, the purpose of this program was to promote better family meals at home for girls attending a summer program by improving the girls’ food preparation skills, and abilities to be family change agents for more healthful family mealtimes.
Keywords: Family meals; Girls; Children; Parents; Nutrition